2020
DOI: 10.1101/2020.04.28.20083428
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Simplified model of Covid-19 epidemic prognosis under quarantine and estimation of quarantine effectiveness

Abstract: A simplified model of Covid-19 epidemic dynamics under quarantine conditions and method to estimate quarantine effectiveness are developed. The model is based on the growth rate of new infections when total number of infections is significantly smaller than population size of infected country or region. The model is developed on the basis of collected epidemiological data of Covid19 pandemic, which shows that the growth rate of new infections has tendency to decrease linearly when the quarantine is imposed in … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Džiugys et al [35] , developed a simplified model using just the Susceptible, Infectious, and Removed (SIR) to quantify the overall effectiveness of the quarantine strategies. They found that their model is effective at evaluating the overall effectiveness of quarantine measures.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Džiugys et al [35] , developed a simplified model using just the Susceptible, Infectious, and Removed (SIR) to quantify the overall effectiveness of the quarantine strategies. They found that their model is effective at evaluating the overall effectiveness of quarantine measures.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Simultaneously, with the spread of the virus, it has become important to analyze mathematically the data not only in Italy but also in other countries [3][4][5][6][7][8]. It is obvious that the a e-mail: feoli@unisannio.it (corresponding author) 0123456789().…”
Section: Introductionmentioning
confidence: 99%
“…Hence we can consider that the effects of lockdown finish two weeks later, at the beginning of June. Simultaneously with the spread of the virus, it has become important to analyze mathematically the data not only in Italy but also in other countries [3][4][5][6][7][8]. It is obvious that the total number of people infected with COVID-19 is impossible to be known exactly.…”
Section: Introductionmentioning
confidence: 99%